Second Five Year Plan Fourth Year's Progress Government of Kerala - Planning Commission (Planning Commission, 1961)
The progress in the implementation of the Plan Schemes in the State Sector during the year 1959-60 was satisfactory. Out of a total budget provision of Rs. 20.68 crores, a sum of Rs. 18.32 crores was spent during the year, bringing the total expenditure under the Second Plan to Rs. 60.30 crores (69% of the outlay) out of the Plan allotment of Rs. 87.01 crores. For central sector schemes an amount of Rs. 1.13 crores was spent during 1959-60 out of a provision of Rs. 1.34 crores.
Government of Kerala